Deportations to the Soviet Union during the 1956 Hungarian revolution according to the KGB documents held in the archives of the Ukrainian Committee for State Security - Natalia Varadi; Вароді Наталія; Váradi Natália (SLOVO\WORD, 2019)
Abstract. After the Second World War, the connection between Hungary, and those who lived in the Soviet Union, was cut, with the strict closing of the borders and the impossibility of traveling. The infrequent communication via post, was strictly checked. The Soviet authorities only allowed the population to subscribe to a few foreign publications, in a small number of copies. Very few people were allowed to buy and even read the Hungarian party press. In Transcarpathia, only a few people dared to speak publicly about the Hungarian revolution in 1956 because it was considered as a crime against the Soviet Communist system. Empathy takes an integral part in the story of the revolution of 1956. Through empathy the Hungarians of Transcarpathia expressed complete identification with the spirit of the Hungarian revolution.
Keywords: Transcarpathia; KGB documents; Hungarian revolution of 1956; Deportations